MORPHOMETRIC VARIATION OF FORAMEN OVALE IN DRY ADULT SKULL OF INDIAN POPULATION WITH CLINICAL CORRELATIONS - AGARWAL, SUMITA; YADAV, ROSHAN KUMAR (International Journal of Current Pharmaceutical Research, 2024)
Objective: The present study aim is to evaluate morphology and morphometric measurements of foramen Ovale present in the Greater wing of Sphenoid bone of the Middle Cranial fossa of the Skull base, using Digital sliding Vernier caliper. The anatomical knowledge of Foramen Ovale and it’s variations are of great help to neurosurgeons, oncologists and radiologists while performing any diagnostic and surgical interventions into and nearby foramen to deal with unavoidable complications as Tic douloureux. Methods: This study was done in 35 dried Human skulls taken from the Department of Anatomy, GBCM, Dehradun, India. The length and the width of the Foramen Ovale were measured. The different shapes of the foramen were also seen. All data collected was subjected to Statistical analysis using Student’s T-test. Results: In the present study, Incidence of Oval shape foramen Ovale was maximum, followed by Elongated shape. There were no statistical differences between the mean length and mean width on the two sides of Foramen Ovale. Conclusion: The vast knowledge of different shapes and sizes of foramen Ovale to Neurosurgeons and Oncologists helps to operate with least invasive procedures to avoid clinical manifestations.